STUDI POTENSI LIMBAH PENGOLAHAN KAYU GERGAJIAN DI KECAMATAN BANJARMASIN UTARA DAN BANJARMASIN BARAT KOTA BANJARMASIN PROVINSI KALIMANTAN SELATAN - Fathul Umar Aditya; Adi Rahmadi; Muhammad Faisal Mahdie (Jurnal Sylva Scienteae, 2020)
This study aims to find out percentage of industrial waste based on its raw materials, to know the types of primary solid waste produced in the sawmill process, to know factors that affect the amount of waste produced, and to estimate the amount of waste to be sample in the 6 trading units (UD) each year. This method by using the snowball sample based on information and permission by the owner of the trading unit to determine the sawmill industry to be used as the object of research. This research was held in 3 Trade Units (UD) sawmill industry in North Banjarmasin sub-district (UD Mitra, UD Sumber Lestari, and also UD Bina Bersama) and 3 sawmill industry using coconut wood in West Banjarmasin sub-district (UD Putra Banjar, UD Hamrani, UD Jaya Bersama). Based on the recapitulation data the average value of log volume, total production and the lowest average percentage of waste wood occurred at UD Bina Bersama by 20.286% with the average waste of each log of 0.272 m3 followed by UD Putra Banjar 0.046 m3 (26.492%), UD Partners 0,315 m3 (26,913%), UD Lestari 0,260 m3 (27,151%), UD Hamrani 0.057 m3 (30,418%), and UD Jaya Bersama 0.057 m3 (31,853%). The main types of solid waste that are in the process of sawmill processing are a piece of wood, a piece of cutting and sawn sawdust. The factors that influence each percentage of waste wood are physical of wood, human resources and use the tools. The estimate of the potential waste studied is at UD Mitra in the amount of 2305,135 m3, at UD Sumber Lestari in the amount of 2124,566 m3, at UD Bina Bersama in the amount of 1587,380 m3, at UD Putra Banjar in the amount of 919,142 m3, at UD Jaya Bersama in the amount of 1359,544 m3, at UD Hamrani in the amount of 1057,870 m3 each year.Keywords: wood waste; sawn timber; waste potential